Effects of an Experimental Seed Treatment from DuPont on Sudden Death Syndrome Symptoms and Soybean Yield - E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2015)
Sudden death syndrome (SDS) is a soybean disease that perennially limits yields in the Kansas River Valley. Soybean cyst nematode (SCN) and saturated soils contribute to the severity of the disease. Selecting varieties with some degree of tolerance to SDS is the only cultural practice that can reduce the severity of SDS and improve yields. Variety selection alone, however, doesn’t necessarily make soybean production profitable; an added complication is managing irrigation scheduling to avoid saturated soils. A study with seed treatments applied to soybean was conducted at the Kansas River Valley Experiment Field in 2014, with treatments applied to two soybean varieties susceptible to SDS. The study was irrigated earlier and more often than normal for soybean to promote the disease. In the most severely infested plots, more than 50% of the leaf area expressed symptoms of SDS by the R6 growth stage. Treatments with an experimental seed treatment from DuPont (Wilmington, DE) reduced the amount of foliar disease in all varieties and increased yields up to 10 bu/a, or more than 25%.
Keywords: soybean sudden death syndrome; seed treatment; soybean yield; Kansas River Valley Experiment Field